Synthesis and photochemical studies of Cu(I) complex with 1,4-bis(3,5-dimethylpyrazol-1yl)tetrazine ligand - GOUNKO, IOURI (SPIE, 2005)
This work reports synthesis and photochemical studies of 3,6-Bis(3,5-dimethylpyrazol-1-yl)-tetrazine ligand (dmptz) and its Cu(I) complex. Dmptz was found to be an excellent bridging ligand for Cu(I) complexes. The Cu(I) complex has been shown to have a dinuclear structure where a single dmptz ligand links two metal centers. It is apparent that the methyl groups of dmptz have a large steric effect on the structure of the complexes preventing the formation of larger tetra- or penta- nuclear complexes reported in the literature for similar ligands (bptz). We have shown that Cu(I) dmptz complexes possess interesting luminescent properties, that might be potentially used to prepare new luminescent materials for sensing and energy conversion applications.
PUBLISHED
Keywords: Chemistry